Examining the relationship between vegetation decline and precipitation in the national parks of the Greater Limpopo Transfrontier Conservation Area during the 21st century - Herrero, Hannah V.; Southworth, Jane; Khatami, Reza; Insalaco, Stephanie; Muir, Carly (Frontiers in Environmental Science, 2023)
The Greater Limpopo Transfrontier Conservation Area (GLTFCA) of southeastern Southern Africa is home to five large national parks and is an important protected area crossing different geopolitical borders, but with the same conservation goals. However, even with similar management techniques, there have been concerning declines in vegetation observed across the last few decades. This study proposes that a larger driver, climate, is linked to this decline over time, and raises the point that these conservation areas are more important now than ever. Precipitation (annual and seasonal), the Normalized Difference Vegetation Index (NDVI, indicator of vegetation health), and Directional Persistence data (D, metric to measure trends in vegetation health over time compared to a baseline value) from 2000-2020 are used. Overall, there was a negative trend in precipitation during the 21st century in all seasons except the beginning of the wet season. Linked to this were negative trends in vegetation health both in absolute NDVI values and resultant D values. Overall, this study found a decline in precipitation, which was significantly linked to a decline in vegetation health across the majority of the year in the GLTFCA. This study supports literature on browning in sub-Saharan Africa and gives managers even more reason to work together towards a unified conservation strategy for this important region.